Impact of human capital and social capital on employability of Chinese college students under COVID-19 epidemic—Joint moderating effects of perception reduction of employment opportunities and future career clarity - Shiyuan, Yang; Jinxiu, Yang; Jingfei, Xu; Yuling, Zhao; Longhua, Yue; Houjian, Li; Wei, Li; Hao, Cheng; Guorong, He; Juan, Chen (Frontiers in Psychology, 2022)
This research constructed a relationship model between human capital, social capital, and the employability of college students. With two moderating variables introduced, the perception reduction of employment opportunities under the COVID-19 epidemic and future career clarity, this research studied the direct impact of human capital and social capital on the employability of college students and boundary conditions. Research data from 810 employed Chinese college graduates shows that both human capital and social capital have a positive and significant impact on the employability; the perception reduction of employment opportunities under the COVID-19 epidemic negatively regulates the relationship between human capital and the employability of college students; the future career clarity positively regulates the relationship between human capital and the employability of college students; the perception reduction of employment opportunities under COVID-19 epidemic and the future career clarity jointly regulate the relationship between human capital, social capital and the employability of college students. These conclusions enrich the relevant theoretical and practical research on the employability of college students under the COVID-19 epidemic.